2(w+2)-w=3(w-1)+9

Simplify each term.

Apply the distributive property.

2w+2⋅2-w=3(w-1)+9

Multiply 2 by 2.

2w+4-w=3(w-1)+9

2w+4-w=3(w-1)+9

Subtract w from 2w.

w+4=3(w-1)+9

w+4=3(w-1)+9

Simplify each term.

Apply the distributive property.

w+4=3w+3⋅-1+9

Multiply 3 by -1.

w+4=3w-3+9

w+4=3w-3+9

Add -3 and 9.

w+4=3w+6

w+4=3w+6

Subtract 3w from both sides of the equation.

w+4-3w=6

Subtract 3w from w.

-2w+4=6

-2w+4=6

Subtract 4 from both sides of the equation.

-2w=6-4

Subtract 4 from 6.

-2w=2

-2w=2

Divide each term in -2w=2 by -2.

-2w-2=2-2

Cancel the common factor of -2.

Cancel the common factor.

-2w-2=2-2

Divide w by 1.

w=2-2

w=2-2

Divide 2 by -2.

w=-1

w=-1

Solve for w 2(w+2)-w=3(w-1)+9